Pengembangan Bahan Ajar Bahasa Arab Berbasis Aplikasi Book Creator dalam Pembelajaran Maharah Qira'ah - Lilik Aisatul Husnah (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
Education in the digital era has a great opportunity to continue innovating and creating interactive and enjoyable learning environments. Conventional learning media that are commonly used need to be enhanced with the latest technology to improve the quality of learning. Therefore, this study aims to develop Arabic language teaching materials in Maharah Qiraah learning based on the Book Creator Application. This study uses a development research method with the Borg & Gall model, which consists of 10 stages: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product testing, 7) product revision, 8) usage testing, 9) product revision, and 10) mass production to develop Arabic language teaching materials in Maharah Qiraah learning based on the Book Creator Application. The Book Creator Application was chosen because it has a file input feature that can be integrated with text, images, audio, and video, creating an interactive and enjoyable learning experience for students. The steps in creating media using Book Creator include concept development, material preparation, design, and distribution. Thus, this study is expected to contribute to the development of innovative and effective learning media in improving the quality of Arabic language learning, particularly in Maharah Qiraah. This study is also expected to increase students' interest and motivation in learning Arabic. Through this research, it is expected that students can gain a more interactive and enjoyable learning experience, which can improve their Maharah Qiraah skills. Additionally, this study can provide a reference for teachers and learning media developers to create innovative and effective learning media.